Current status and advances in zinc anodes for rechargeable aqueous zinc-air batteries - Muhammad Afiq Irfan Mohd Shumiri; Abdillah Sani Mohd Najib; Nor Akmal Fadil (Science and Technology of Advanced Materials)
To promote sustainable development and reduce fossil fuel consumption, there is a growing demand for high-performance, cost-effective, safe and environmentally friendly batteries for large-scale energy storage systems. Among the emerging technologies, zinc-air batteries (ZABs) have attracted significant interest. By integrating the principles of traditional zinc-ion batteries and fuel cells, ZABs offer remarkably high theoretical energy density at lower production cost compared to the current state-of-the-art lithium-ion batteries (LIBs). However, the critical challenge remains in developing high-performance zinc anode. Herein, this review provides a comprehensive analysis of the current status and advancements in zinc anodes for rechargeable aqueous ZABs. We begin by highlighting the major challenges and underlying mechanisms associated with zinc anodes including issues such as uneven zinc deposition, dendrite growth and hydrogen evolution reaction. Then, this review discusses the recent advancements in zinc anode modifications, focusing on strategies such as alloying, surface porosity and zincophilicity. By reviewing the latest research, we also identify existing gaps and pose critical questions that need further exploration to push the field forward. The goal of this review is to inspire new research directions and promote the development of more efficient zinc anodes.